The Effect of Omega-3 Medication on Autistic Children in Riyadh, Saudi Arabia - Alnami, Maryam Alhassan; Alswayegh, Maram Abdulmohsen (Journal of medical and pharmaceutical sciences, 2023)
This comprehensive review article explores the effect of omega-3 medication on autistic children in Riyadh, Saudi Arabia. Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder characterized by challenges in social communication and repetitive behaviors. Traditional treatment approaches for ASD have limitations, necessitating the exploration of alternative treatments. Omega-3 fatty acids, which are essential nutrients found in certain foods, have been associated with various health benefits, including potential benefits for managing ASD symptoms.The review begins by providing a detailed overview of the prevalence and characteristics of ASD, as well as the current treatment approaches and their limitations. It emphasizes the importance of exploring alternative treatments for ASD due to the need for more effective interventions.Next, the article delves into an in-depth exploration of omega-3 fatty acids, explaining their sources, types, and associated health benefits. The role of omega-3 supplementation in managing ASD symptoms is discussed, highlighting the potential mechanisms through which omega-3 fatty acids may exert their effects on the neurodevelopmental processes relevant to ASD.To support the potential benefits of omega-3 supplementation for autistic children, the review examines relevant research studies conducted on this topic. A comprehensive review of randomized controlled trials (RCTs), systematic reviews, and meta-analyses is provided, summarizing the key findings and conclusions. The review explores the varied outcomes observed in terms of improvements in social interaction, communication, and repetitive behaviors in autistic children after omega-3 supplementation. It also discusses the limitations and gaps in the existing research, highlighting the need for further studies to provide a clearer understanding of the effects of omega-3 medication on ASD symptoms.
Keywords: children; Omega-3 medication; Autistic; Riyadh; Saudi Arabia; autism spectrum disorder (ASD)